Seeds of heaven - Henry, Kim, 1961-; Lard, Mary Anne (Harrisburg, PA : Morehouse Pub., 1999)
As a boy and his father walk from their home to the seashore, they witness the wonders of all God has made. Includes selected Bible verses.
3.0
K-3
K-3
Keywords: Nature -- Religious aspects -- Christianity -- Juvenile literature; Creation -- Juvenile literature; Jesus Christ -- Parables -- Juvenile literature; Nature -- Religious aspects -- Christianity; Creation; Nature -- Religious aspects